![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{\sqrt{a}-a}{a\sqrt{a}-a+\sqrt{a}}:\frac{1}{a^2+\sqrt{a}}\)
\(=\frac{\sqrt{a}\left(1-\sqrt{a}\right)}{\sqrt{a}\left(a-\sqrt{a}+1\right)}.\frac{\sqrt{a}\left(a\sqrt{a}+1\right)}{1}\)
\(=\frac{1-\sqrt{a}}{a-\sqrt{a}+1}.\frac{\sqrt{a}\left(\sqrt{a}+1\right)\left(a-\sqrt{a}+1\right)}{1}\)
\(=\sqrt{a}\left(1-\sqrt{a}\right)\left(\sqrt{a}+1\right)\)
\(=\sqrt{a}\left(1-\sqrt{a}\right)\left(1+\sqrt{a}\right)\)
\(=\sqrt{a}\left(1-a\right)\)
\(=\sqrt{a}-a\sqrt{a}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Điều kiện: x \(\ne\) 1; 1/4 ; x \(\ge\) 0
\(A=1+\left(\frac{\left(2a+\sqrt{a}-1\right)}{\left(1-\sqrt{a}\right)\left(1+\sqrt{a}\right)}-\frac{\left(2a+\sqrt{a}-1\right).\sqrt{a}}{\left(1-\sqrt{a}\right)\left(a+\sqrt{a}+1\right)}\right)\left(\frac{\sqrt{a}\left(\sqrt{a}-1\right)}{2\sqrt{a}-1}\right)\)
\(A=1+\left(\frac{\left(2a+\sqrt{a}-1\right)\left(a+\sqrt{a}+1\right)-\left(2a+\sqrt{a}-1\right)\left(1+\sqrt{a}\right).\sqrt{a}}{\left(1-\sqrt{a}\right)\left(1+\sqrt{a}\right)\left(a+\sqrt{a}+1\right)}\right)\left(\frac{\sqrt{a}\left(\sqrt{a}-1\right)}{2\sqrt{a}-1}\right)\)
\(A=1+\left(\frac{\left(2a+\sqrt{a}-1\right)\left(a+\sqrt{a}+1-a-\sqrt{a}\right)}{\left(1-\sqrt{a}\right)\left(1+\sqrt{a}\right)\left(a+\sqrt{a}+1\right)}\right)\left(\frac{\sqrt{a}\left(\sqrt{a}-1\right)}{2\sqrt{a}-1}\right)\)
\(A=1+\left(\frac{\left(2a+\sqrt{a}-1\right)}{\left(1-\sqrt{a}\right)\left(1+\sqrt{a}\right)\left(a+\sqrt{a}+1\right)}\right)\left(\frac{\sqrt{a}\left(\sqrt{a}-1\right)}{2\sqrt{a}-1}\right)\)
\(A=1+\left(\frac{\left(2\sqrt{a}-1\right)\left(\sqrt{a}+1\right)}{\left(1-\sqrt{a}\right)\left(1+\sqrt{a}\right)\left(a+\sqrt{a}+1\right)}\right)\left(\frac{-\sqrt{a}\left(1-\sqrt{a}\right)}{2\sqrt{a}-1}\right)=1+\frac{-\sqrt{a}}{a+\sqrt{a}+1}=\frac{a+1}{a+\sqrt{a}+1}\)
Các bài tập dạng này hoàn toàn làm tương tự!!!
ĐK: a \(\ge\)1
\(\sqrt{a+2\sqrt{a-1}}+\sqrt{a-2\sqrt{a-1}}\)
\(=\sqrt{a-1+2\sqrt{a-1}+1}+\sqrt{a-1-2\sqrt{a-1}+1}\)
\(=\sqrt{\left(\sqrt{a-1}+1\right)^2}+\sqrt{\left(\sqrt{a-1}-1\right)^2}\)
= \(\sqrt{a-1}+1+\left|\sqrt{a-1}-1\right|\)
Xét a \(\ge\)2 => \(\sqrt{a+2\sqrt{a-1}}+\sqrt{a-2\sqrt{a-1}}=\sqrt{a-1}+1+\sqrt{a-1}=2\sqrt{a-1}\)
Xét \(0\le a< 2\) => \(\sqrt{a+2\sqrt{a-1}}+\sqrt{a-2\sqrt{a-1}}=\sqrt{a-1}+1+1-\sqrt{a-1}=2\)